Modelling the impact of traffic emissions on local air quality - Ganguly, Rajiv (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2008)
Air quality modelling can be used to complement monitoring networks and to obtain information at lower cost. A primary advantage of modelling is that it can be used for the prediction of future air quality, which often forms an important part of Environmental Impact Assessment (EIA) studies. The research described in this thesis represents an in - depth atmospheric dispersion modelling study carried out at highway and street canyon locations in the Dublin area for the pollutants CO, NOx and NO2. In this context, appropriate dispersion models GFLSM and CALINE4 for highways and STREET and OSPM models were studied and validated for local conditions.
Keywords: Civil Engineering, Ph.D.; Ph.D. Trinity College Dublin